OP0176 HEALTH-RELATED QUALITY OF LIFE IN HAND OSTEOARTHRITIS PATIENTS FROM THE GENERAL POPULATION AND THE OUTPATIENT CLINIC. (June 2019) - Loef, Marieke; Damman, Wendy; Mutsert, Renée de; Rosendaal, Frits; Kloppenburg, Margreet
Abstract : Background: In osteoarthritis (OA) patients health-related quality of life (HRQoL) is decreased. Whether patients with OA seeking care in a rheumatology outpatient clinic experience more impact on HRQoL than those in the general population is unknown. Objectives: To investigate the impact of hand OA on physical and mental HRQoL in the general population, and to investigate the difference in impact between patients who have, and who have not been referred to a medical specialist. Methods: In the population-based Netherlands Epidemiology of Obesity (NEO) study, middle-aged participants were recruited from the greater area of Leiden. In the Hand OSTeoArthritis in Secondary care (HOSTAS) study, patients with a rheumatologist's diagnosis of primary hand OA were recruited from the outpatient clinic at the Leiden University Medical Center, a secondary and tertiary referral center. In both cohorts, hand and knee OA was defined by the ACR clinical classification criteria. Patients with fibromyalgia or inflammatory rheumatic conditions were excluded. Fur the current analyses, only patients classified with hand OA alone were included. HRQoL was measured with the SF-36 questionnaire; we calculated standardized scores on a scale of 0 to 100 with subsequent application of a norm-based transformation (mean 50, standard deviation 10). Linear regression analyses, corrected for age, sex, education, ethnicity and BMI, were used to study cross-sectional associations between OA and HRQoL. Data are presented as regression coefficients with 95% confidence intervals (CI). Because a suitable reference group without OA was lacking in the HOSTAS study, these patients were compared to the normative value of 50. Previous research concluded a minimal clinically important difference of 2 points on the SF-36 scale, which was used to assess clinical relevance of differences in scores. Results: Of the 6, 334 NEO participants 8% were classified with only hand OA and 4% were classified concurrent hand and knee OA. The HOSTAS cohort consisted of a total of 538 patients with hand OA, of whom 57% fulfilled the ACR criteria for only hand OA and 32% was defined with concurrent hand and knee OA. In the population-based NEO study, mean PCS was reduced with -2.4 (-3.6; -1.3) in participants with only hand OA, compared to participants without hand or knee OA (table 1). The subscales bodily pain and physical functioning were affected the most with mean differences of –3.4 (-4.6; -2.2) and -2.1 (-3.0; -1.1). Mental HRQoL was not reduced in participants with only hand OA, compared to participants without OA. In the population-based cohort 14% of participants with hand OA reported to have visited a medical specialist for OA. Participants with hand OA that have been referred to a medical specialist showed a lower physical HRQoL with a mean difference in the PCS of –3.9 (-6.7; -1.2), but no difference in mental HRQoL, compared with participants with hand OA that have not reported consulting secondary care for OA (table 2). In patients with only hand OA from the outpatient clinic, the PCS (-3.5), bodily pain (-4.9), vitality (-2.5) and role functioning – physical (-2.2) scales were clinically relevantly reduced, but mental HRQOL was not affected. Conclusion: Participants with hand OA from the general population had a clinically relevant lower physical HRQoL, but not mental HRQoL. Physical HRQoL was further reduced in patients consulting secondary care and in co-occurrence with knee OA. Hence, patients with hand OA in secondary care experience more impact on physical HRQoL than patients in the general population. Disclosure of Interests: : Marieke Loef Grant/research support from: Innovative Medicines Initiative Joint Undertaking under Grant Agreement n° 115770, Wendy Damman: None declared, Renée de Mutsert: None declared, Frits Rosendaal: None declared, Margreet Kloppenburg Grant/research support from: Pfizer, IMI-APPROACH (Grant Agreement n° 115770), Consultant for: GlaxoSmithKline, Merck-Serono, Abbvie, Levicept, Pfizer